Protection Against Cyberbullying for Teens in the United States - Ramadhani, Shahnata Putri Dwi; Prastyanti, Rina Arum (The Easta Journal Law and Human Rights, 2024)
Cyberbullying, also known as cyberbullying, is any form of violence experienced by a child or adolescent and perpetrated by peers their age through the internet or cyberspace. If a child or teenager is teased, insulted, bullied, or humiliated by another child or youth through the medium of the internet, digital technology, or cell phones, this is also known as cyber bullying. This research uses a literature study approach to explore it, this approach involves the disclosure of a comprehensive literature to sources relevant to cyberbullying cases in the United States. In achieving the research objectives, the main focus will also be given to factors affecting cyberbullying and protection efforts from cyberbullying as well as the United States' policy in handling cyberbullying cases among adolescents. There are several factors that can influence the occurrence of cyberbullying in adolescents. Some of these include individual factors including experience of violence, perception, gander, age, psychological control, and additive use. Family factors include parenting, family support, and parental stress. The friend factor is support. The school factor is the type of school. The last factor is the use of the internet in the form of intensity and competence of ethical media. There are also cyberbullying protection measures for adolescents and U.S. policies in handling cyberbullying cases among adolescents. Cyberbullying is an increasing concern affecting young people around the world, particularly in the United States. To address this issue, it is important to develop comprehensive strategies and support systems that address the root causes of cyberbullying and encourage positive social interactions.